2008
DOI: 10.1016/j.molcel.2008.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct eRF3 Requirements Suggest Alternate eRF1 Conformations Mediate Peptide Release during Eukaryotic Translation Termination

Abstract: Organisms that use the standard genetic code recognize UAA, UAG, and UGA as stop codons, whereas variant code species frequently alter this pattern of stop codon recognition. We previously demonstrated that a hybrid eRF1 carrying the Euplotes octocarinatus domain 1 fused to Saccharomyces cerevisiae domains 2 and 3 (Eo/Sc eRF1) recognized UAA and UAG, but not UGA, as stop codons. In the current study, we identified mutations in Eo/Sc eRF1 that restore UGA recognition and define distinct roles for the TASNIKS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
82
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 30 publications
5
82
0
Order By: Relevance
“…In general, these species either utilize UGA as a stop codon (with UAA and UAG recoded to glutamine codons) (Horowitz and Gorovsky 1985;Lozupone et al 2001;Kim et al 2005) or UAA/UAG as stop codons (with UGA recoded to cysteine or tryptophan codons) (Meyer et al 1991;Lozupone et al 2001). Past studies found that fusion of eRF1 domain one from a variant code organism to eRF1 domains two and three from a standard code organism often conferred variant stop codon recognition (Kervestin et al 2001;SalasMarco et al 2006;Lekomtsev et al 2007a,b;Fan-Minogue et al 2008;Eliseev et al 2011). These results demonstrated that eRF1 domain one plays a key role in stop codon recognition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, these species either utilize UGA as a stop codon (with UAA and UAG recoded to glutamine codons) (Horowitz and Gorovsky 1985;Lozupone et al 2001;Kim et al 2005) or UAA/UAG as stop codons (with UGA recoded to cysteine or tryptophan codons) (Meyer et al 1991;Lozupone et al 2001). Past studies found that fusion of eRF1 domain one from a variant code organism to eRF1 domains two and three from a standard code organism often conferred variant stop codon recognition (Kervestin et al 2001;SalasMarco et al 2006;Lekomtsev et al 2007a,b;Fan-Minogue et al 2008;Eliseev et al 2011). These results demonstrated that eRF1 domain one plays a key role in stop codon recognition.…”
Section: Introductionmentioning
confidence: 99%
“…1A; Knight et al 2000;Song et al 2000;Lozupone et al 2001;Kim et al 2005), suggesting that these sequence elements play a role in stop codon recognition. Mutagenesis studies examined the effects of changing amino acids within the TASNIKS and YCF motifs of eRF1 (Bertram et al 2000;Frolova et al 2002;Seit-Nebi et al 2002;Kolosov et al 2005;Fan-Minogue et al 2008;Cheng et al 2009). Those studies confirmed the general importance of both motifs in stop codon recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M domain mimics the tRNA acceptor stem and contains a universal GGQ motif common to all class-1 RFs, which is located at the tip of the M domain of eRF1 and is essential for peptidyl-tRNA hydrolysis at the peptidyl transferase center Song et al 2000;Seit-Nebi et al 2001;Klaholz et al 2003;Mora et al 2003;Rawat et al 2003;Scarlett et al 2003;Petry et al 2005). The N domain mimics the tRNA anticodon arm and contains two loops with the highly conserved YxCxxxF (positions 125-131) and NIKS (positions 61-64) motifs that play a critical role in stop-codon recognition Ito et al 2002;Seit-Nebi et al 2002;Kolosov et al 2005;Fan-Minogue et al 2008;Cheng et al 2009). Evidence that the first nucleotide of a stop codon at the A site contacts K63 in the NIKS motif of human eRF1 has been obtained (Chavatte et al 2002) by cross-linking experiments with an mRNA analog containing a 4-thiouridine (s 4 U) residue at the first position of the stop codon phased on the ribosome by a tRNA Asp cognate to the Asp codon, which is located 59 to the stop codon (Chavatte et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The N domain is responsible for stop codon recognition, which is achieved through a 3D network of conserved residues that include apical TASNIKS (amino acid sequence: threonine-alanine-serine-asparagine-isoleucine-lysine-serine) and YxCxxxF motifs (e.g., refs. [9][10][11][12]. Domain M contains the universally conserved GGQ motif, which is critical for triggering peptide release: as shown for prokaryotes, its placement into the peptidyl transferase center (PTC) causes rRNA rearrangement, allowing a water molecule to enter (for review, see ref.…”
mentioning
confidence: 99%